2012
DOI: 10.1158/1535-7163.mct-11-0474
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of NVP-BKM120, an Orally Available Pan-Class I PI3-Kinase Inhibitor

Abstract: Following the discovery of NVP-BEZ235, our first dual pan-PI3K/mTOR clinical compound, we sought to identify additional phosphoinositide 3-kinase (PI3K) inhibitors from different chemical classes with a different selectivity profile. The key to achieve these objectives was to couple a structure-based design approach with intensive pharmacologic evaluation of selected compounds during the medicinal chemistry optimization process. Here, we report on the biologic characterization of the 2-morpholino pyrimidine de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
395
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 484 publications
(416 citation statements)
references
References 43 publications
(39 reference statements)
16
395
1
4
Order By: Relevance
“…preclinical studies have suggested that PIK3CA mutations might predict sensitivity to pan-PI3K and dual PI3K/mTOR inhibitors (25); however, these results have not yet been clinically validated. In contrast, studies with a-isoformselective and b-isoform-sparing PI3K inhibitors have produced responses among patients with tumors harboring PIK3CA mutations (26,27); in addition, the presence of a PIK3CA mutation-related gene signature may identify patients with breast cancer who may benefit from the addition of everolimus to letrozole (28), although clinical benefit from everolimus is not restricted to patients with PIK3CA-mutant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…preclinical studies have suggested that PIK3CA mutations might predict sensitivity to pan-PI3K and dual PI3K/mTOR inhibitors (25); however, these results have not yet been clinically validated. In contrast, studies with a-isoformselective and b-isoform-sparing PI3K inhibitors have produced responses among patients with tumors harboring PIK3CA mutations (26,27); in addition, the presence of a PIK3CA mutation-related gene signature may identify patients with breast cancer who may benefit from the addition of everolimus to letrozole (28), although clinical benefit from everolimus is not restricted to patients with PIK3CA-mutant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, AMP-dependent protein kinase; GF, growth factor; GRB2, growth factor receptor-bound protein 2; IRS1, insulin receptor substrate 1; PDK1, phosphoinositide-dependent kinase 1; PIP2, phosphatidylinositol 4,5-bisphosphate; PIP3, phosphatidylinositol 3,4,5-trisphosphate. (Continued on the following page) (6,7), and no clinical responses with these compounds have been observed in patients with PTEN-altered tumors in single-agent phase I trials (8,9). In contrast, 1 of the 2 patients who experienced a partial response in the phase I single-agent trial of BEZ235 had non-small cell lung cancer (NSCLC) with PTEN mutation (10).…”
Section: Tumors With Alterations In Ptenmentioning
confidence: 99%
“…Buparlisib has demonstrated antiproliferative, proapoptotic, and antiangiogenic activity in multiple preclinical cancer models [46]. Buparlisib demonstrates synergistic activity with cytotoxic and targeted agents [46,47], and enhances sensitivity to these drugs in resistant cancer models [48].…”
Section: Pan-pi3k Inhibitionmentioning
confidence: 99%